The effect of gadolinium doping on the structural, magnetic and photoluminescence properties of electrospun bismuth ferrite nanofibers. Issue 10 (December 2015) - George Philip, Geo; Senthamizhan, Anitha; Srinivasan Natarajan, Thirupathur; Chandrasekaran, Gopalakrishnan; Annal Therese, Helen
Abstract: Gadolinium (Gd) doped Bismuth ferrite (BFO) nanofibers (Bi1− x Gd x FeO3 ( x =0.0, 0.05, 0.10, 0.15 and 0.20)) were synthesized via electrospinning. Scanning Electron Microscope (SEM) analysis showed that the diameter of the nanofibers ranged from 150 to 250 nm. X-Ray Diffraction (XRD) analysis revealed a structural phase transition with varying ' x ', the compositions with x ≤0.10 have crystal structures with space group R3c, while the compositions with x >0.10 have crystal structures with space group Pnma. Vibrating Sample Magnetometer (VSM) analysis exhibited the weak ferromagnetic nature of the BFO nanofibers. However an increase in the saturated magnetic moment with increase in Gd dopant concentration was observed. The Photoluminescence (PL) spectra of the Bi1− x Gd x FeO3 nanofibers show enhanced Near Band Emission (NBE) intensity at x =0.10 due to the passivation of oxygen vacancies by Gd doping.